2017
DOI: 10.1289/ehp1275
|View full text |Cite|
|
Sign up to set email alerts
|

Regulation of Chromatin Assembly and Cell Transformation by Formaldehyde Exposure in Human Cells

Abstract: Background:Formaldehyde (FA) is an environmental and occupational chemical carcinogen. Recent studies have shown that exogenous FA causes only a modest increase in DNA adduct formation compared with the amount of adducts formed by endogenous FA, raising the possibility that epigenetic mechanisms may contribute to FA-mediated carcinogenicity.Objectives:We investigated the effects of FA exposure on histone modifications and chromatin assembly. We also examined the role of defective chromatin assembly in FA-media… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 68 publications
2
19
0
Order By: Relevance
“…The ability of FA to react with histone lysine residues reported by Yoshida et al [30] and Chen et al [31] are in line with previous results obtained by Lu et al [45] in a simplified in vitro model employing H4 isolated from calf thymus tissues and human recombinant H4 purified after expression in E. Coli. The authors, in fact, demonstrated that the FA-induced lysine adducts on histone may impair post-transcriptional histone acetylation and deacetylation balance.…”
Section: Histone Modificationssupporting
confidence: 91%
See 4 more Smart Citations
“…The ability of FA to react with histone lysine residues reported by Yoshida et al [30] and Chen et al [31] are in line with previous results obtained by Lu et al [45] in a simplified in vitro model employing H4 isolated from calf thymus tissues and human recombinant H4 purified after expression in E. Coli. The authors, in fact, demonstrated that the FA-induced lysine adducts on histone may impair post-transcriptional histone acetylation and deacetylation balance.…”
Section: Histone Modificationssupporting
confidence: 91%
“…In this context, FA may impact post-transcriptional modifications disturbing the recruitment of regulatory complexes and evolving into an aberrant chromatin assembly that may facilitate anchorage-independent growth of cells. These data suggest that compromising chromatin assembly, through inhibition of lysine acetylation, may dysregulate cancer-related gene expression, as a possible new mechanism underlying FA-induced carcinogenesis [31]. The identification of FA reactive sites on histones is an initial step in understanding additional mechanisms of FA toxicity and carcinogenicity [59].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations